Training on Cultivation of Organic Food Crops for the KWT Fajar Ayu Group and the Podo Rukun Farmer Group - Anjarwati, Sulis; Wahidah, Nina Ikhwati; Khoriudin, M; Sutanto, Agus; ., Achyani; ., Riswanto (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Training on Cultivation of Organic Food Crops for the KWT Fajar Ayu Group and the Podo Rukun Farmer Group is an effort to increase farmers' understanding and skills in organic farming practices. This community service aims to identify the influence of this training on increasing organic food crop production as well as farmers' understanding and practices related to organic farming. This community service is carried out through socialization and discussions about organic plant cultivation, practice organic vegetable cultivation and program evaluation. The results of this community service show that training in organic food crop cultivation has had a positive impact on increasing organic food crop production, reducing the use of dangerous chemicals, and increasing farmers' understanding of organic farming practices. Apart from that, this training also contributes to increasing farmers' income and their welfare. Thus, training in organic food crop cultivation is an effective step in encouraging sustainable agricultural practices, which have the potential to increase food security and farmer welfare. The results of this community service can be an important reference for the government, agricultural institutions and other farmer groups in their efforts to promote organic farming as a sustainable solution in meeting people's food needs.